Effectiveness of specific professional training in male elite adolescent team handball players - Wagner, H.; Radic, V.; Hinz, M. (Sports, 2025)
Professional training in elite team handball academies is key to developing top players, yet its direct impact on physical performance remains unclear. This study aimed to (1) provide professional training to elite adolescent players and (2) assess performance improvements using a team handball-specific test. Thirty elite male players (six goalkeepers, 24 field players) participated in an 11-week program, with nine under-19 (17.2 ± 1.3 years) and nine under-17 (15.6 ± 0.9 years) field players completing at least 80% of sessions. All underwent pre- and post-testing using the game-based performance test. A two-way ANOVA analyzed differences between tests and age groups as well as playing positions. Significant improvements (p < 0.05) were found in defense and offense time and body weight for both groups. Under-17 players also showed a significant increase in peak oxygen uptake (+9%), ball velocity (+7%), and jump height (+20%). Agility in defense and offense improved in under-19 (+3%) and under-17 (+6%) players, aligning with training goals. Positional differences were observed between backcourt players and wings (p < 0.01) in the ball velocity, while all players showed improvements in both defense and offense performance. We suggest that professional and targeted specific training at this age has a significant impact on the long-term development of adolescent team handball players and is the basis for a professional handball career.